Visible light active Zr- and N-doped TiO2 coupled g-C3N4 heterojunction nanosheets as a photocatalyst for the degradation of bromoxynil and Rh B along with the H2 evolution process. Issue 22 (4th October 2021) - Pahi, Souman; Sahu, Sumanta; Singh, Satish Kumar; Behera, Abhijit; Patel, Raj Kishore
Abstract : The light harvesting abilities of TiO2 has been drastically increased by creating a defect level with doping using zirconium (Zr) and nitrogen (N). Abstract : Herein, we drastically increased the l ight-harvesting abilities of TiO2 by creating a defect level with doping using zirconium (Zr) and nitrogen (N). Titanium was substantially replaced by Zr from its lattice point, and N was bound on the surface as (NO)x . The doped system comes with a reduced band edge of 2.8 eV compared to pure TiO2 (3.2 eV), and the doping was accompanied by a higher rate of recombination of photogenerated electron–hole pairs. A heterostructure was fabricated between the modified titania and g-C3 N4 to efficiently separate the carriers. An easy and cost-effective sol–gel process followed by a co-calcination technique was used to synthesize the nanostructured composite. The optimum dopant concentration and the extent of doping were investigated via XRD, Raman, XPS, TEM, and PL analyses, followed by a photocatalytic study. The impact of the band positions was investigated via UV-DRS and EIS. The dynamic nature of the band alignment at the depletion region of the heterojunction increased the carrier mobility from the bulk to active sites. The photogenerated electrons and holes retained their characteristic redox abilities to generate both OH˙ and O2 − ˙ through a z-scheme mechanism. The photocatalytic activity resulted in superior photocatalytic H2 evolution along with the defragmentation of bromoxynil, a persistent herbicide. The active catalyst exhibited 97% degradation efficiency towards pollutants along with 0.86% apparent quantum efficiency during the H2 evolution reaction.